2001
DOI: 10.1063/1.1335830
|View full text |Cite
|
Sign up to set email alerts
|

Analytical theory of frequency-multiplying gyro-traveling-wave-tubes

Abstract: The theory is developed which describes analytically the gain and bandwidth in frequency-multiplying gyro-traveling-wave-tubes. In this theory the input waveguide is considered in the small-signal approximation. Then, in the drift region separating the input and output waveguides, the electron ballistic bunching evolves which causes the appearance in the electron current density of the harmonics of the signal frequency. The excitation of the output waveguide by one of these harmonics is considered in a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…By amplifying a drive wave through interaction at the fundamental cyclotron harmonic frequency, the beam-embedded nonlinear signal at a harmonic frequency is amplified through sequent harmonic interaction. [10][11][12] Experimental results have indicated that a third harmonic multiplying gyro-TWA, operating at an input frequency range of 11.1-11.5 GHz, produced an output power of approximately 15 dBm. 13 A subsequent study demonstrated that a Ka-band harmonic-multiplying gyro-TWA produced a peak output power of 75 kW with a bandwidth of 1.06% and a gain of 25 dB.…”
Section: Introductionmentioning
confidence: 99%
“…By amplifying a drive wave through interaction at the fundamental cyclotron harmonic frequency, the beam-embedded nonlinear signal at a harmonic frequency is amplified through sequent harmonic interaction. [10][11][12] Experimental results have indicated that a third harmonic multiplying gyro-TWA, operating at an input frequency range of 11.1-11.5 GHz, produced an output power of approximately 15 dBm. 13 A subsequent study demonstrated that a Ka-band harmonic-multiplying gyro-TWA produced a peak output power of 75 kW with a bandwidth of 1.06% and a gain of 25 dB.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in terms of gyro-traveling-wave tube, of the electron beam's axial velocity fragmentation is a very serious problem [9] . Therefore, generating low-speed maneuvering scattered electron beam is the key to design high performance gyro-traveling-wave tube amplifier.…”
Section: I-introductionmentioning
confidence: 99%
“…The harmonic multiplying operation is of practical interest because of the reduced magnetic-field requirement and the ready availability of lowfrequency drivers for a gyrotron traveling wave amplifier. Theoretical studies and numerical simulation had been made in the references [6,8,10,11] for frequency-doubling amplifier. It had been shown that harmonic multiplying amplifiers were nonlinear devices possessing characteristics fundamentally different from those of a single-frequency amplifier.…”
mentioning
confidence: 99%